Combinatorial Strategy for Studying Biochemical Pathways in Double Emulsion Templated Cell‐Sized Compartments. Issue 48 (27th October 2020) - dos Santos, Elena C.; Belluati, Andrea; Necula, Danut; Scherrer, Dominik; Meyer, Claire E.; Wehr, Riccardo P.; Lörtscher, Emanuel; Palivan, Cornelia G.; Meier, Wolfgang
Abstract: Cells rely upon producing enzymes at precise rates and stoichiometry for maximizing functionalities. The reasons for this optimal control are unknown, primarily because of the interconnectivity of the enzymatic cascade effects within multi‐step pathways. Here, an elegant strategy for studying such behavior, by controlling segregation/combination of enzymes/metabolites in synthetic cell‐sized compartments, while preserving vital cellular elements is presented. Therefore, compartments shaped into polymer GUVs are developed, producing via high‐precision double‐emulsion microfluidics that enable: i) tight control over the absolute and relative enzymatic contents inside the GUVs, reaching nearly 100% encapsulation and co‐encapsulation efficiencies, and ii) functional reconstitution of biopores and membrane proteins in the GUVs polymeric membrane, thus supporting in situ reactions. GUVs equipped with biopores/membrane proteins and loaded with one or more enzymes are arranged in a variety of combinations that allow the study of a three‐step cascade in multiple topologies. Due to the spatiotemporal control provided, optimum conditions for decreasing the accumulation of inhibitors are unveiled, and benefited from reactive intermediates to maximize the overall cascade efficiency in compartments. The non‐system‐specific feature of the novel strategy makes this system an ideal candidate for the development of new synthetic routes as well as for screening natural and more complex pathways. Abstract : The novel combinatorial strategy for studying enzymatic cascade reactions inside synthetic compartments, produced via high‐precision double‐emulsion microfluidics can be applied to any multi‐step cascades, and enables discovering unwanted pathways, detecting undesirable intermediates, and identifying routes for rapid toxins consumption. Such appealing aspects will enhance capabilities of biotechnological applications as enzyme replacement therapy, biological detoxification, chemical synthesis, and biosensors.